Perbandingan Cosine Similarity dan Weighted Jaccard Similarity dalam Pengembangan Mesin Pencari Perpustakaan Digital - Pamput, Jessicha Putrianingsih; Muthmainnah, Aindri Rizky; Surianto, Dewi Fatmarani; Fadilah, Nur (Politeknik Harapan Bersama, 2025)
This study addressed the problem of low relevance in search results within the digital library system of the Department of Informatics and Computer Engineering (JTIK), Universitas Negeri Makassar. The purpose of this research was to improve the accuracy and relevance of search outcomes, enabling users, particularly students, to access academic materials and research references more efficiently. A search engine system was developed using a term-weighting method based on term frequency and document distribution. The system incorporated similarity measurement techniques to evaluate the degree of match between user queries and document content. An experimental approach was applied, which involved observation, data collection, text preprocessing, implementation of term weighting, and the comparison of cosine similarity and Weighted Jaccard similarity for ranking search results. The The evaluation was conducted using the Precision@K metric and a paired t-test to measure the significance of performance differences between methods. The test results showed that Weighted Jaccard obtained an average Precision@K value of 0.933, slightly higher than Cosine Similarity with an average of 0.9. However, Cosine Similarity produced a higher average similarity value. In addition, system testing was conducted in two stages, namely assessing user satisfaction with search results and assessing system performance. These findings confirmed that the combination of term-weighting and cosine similarity effectively enhanced the relevance and performance of digital library search systems.